Automobile demand and supply in Brazil: Effects of tax rebates and trade liberalization on price-marginal cost markups in the 1990s - Eduardo P. S. Fiuza (Institute for Applied Economic Research (ipea), 2015)
This work is a pioneer effort to estimate supply and demand of automobiles in Brazil with a Discrete Choice model in a differentiated product oligopolistic market. We apply a Nested Logit model to the demand side and assume differentiated product price-setting firms on the supply side to evaluate the severe transformations undergone by the Brazilian automobile industry in the 1990s, especially policy events such as the tax rebates created for the so-called popular models (introduced in 1993) and the trade liberalization (initiated in 1991 and partially reversed in 1995 under the so-called Automotive Regime). We find that, although domestic cars still enjoyed considerably higher price-marginal cost markup rates than their imported counterparts (net of VATs and duties) in all market segments at the end of our sample (1997), these rates had dropped drastically and permanently during the 1995 import boom, not only because of import, but also from fiercer domestic competition. A perhaps striking finding is that, as opposed to what was verified in studies for other countries, popular and compacts enjoy the highest price-marginal cost markup rates, as they are significantly less threatened by imported competitors than the larger and luxurious models. These rates do not translate into higher pricecost margins in money units, but due to their high sales volumes these models account for great shares of the firms' profits.
Keywords: 330